Effect of microbial inoculation on nutrient turnover and lignocellulose degradation during composting: A meta-analysis. (15th April 2021) - Nigussie, Abebe; Dume, Bayu; Ahmed, Milkyas; Mamuye, Melkamu; Ambaw, Gebermedihin; Berhiun, Goytom; Biresaw, Armaye; Aticho, Abebayheu
Highlights: Meta-analysis was performed to determine inoculants effect on compost quality. The mean effect size for lignocellulose degradation ranged between +40% and +65% The mean effect was +30% for total nitrogen and +46% for total phosphorus. Microbial inoculants have limited effect on bioavailable nutrient concentration. Experimental setups, biotic and abiotic factors influence inoculants efficiency. Abstract: Although microbial inoculants are promoted as a strategy for improving compost quality, there is no consensus in the published literature about their efficacy. A quantitative meta -analysis was performed to estimate the overall effect size of microbial inoculants on nutrient content, humification and lignocellulosic degradation. A meta -regression and moderator analyses were conducted to elucidate abiotic and biotic factors controlling the efficacy of microbial inoculants. These analyses demonstrated the beneficial effects of microbial inoculants on total nitrogen (+30%), total phosphorus (+46%), compost maturity index (C:N ratio (-31%), humification (+60%) and the germination index (+28%). The mean effect size was −46%, −65% and −40% for cellulose, hemicellulose, and lignin respectively. However, the effect size was marginal for bioavailable nutrient concentrations of phosphate, nitrate, and ammonium. The effectiveness of microbial inoculants depends on inoculant form, inoculation time, composting method, and experimental duration. The microbial inoculant effect size was consistent under different feedstock types and experimental scales. These findings imply that microbial inoculants are important for accelerating lignocellulose degradation. Higher mean effect sizes have tended to be published in journals with higher impact factors, thus researchers should be encouraged to publish non-significant findings in order to provide a more reliable estimation of effect size and clarify doubts about the benefits of microbial inoculants for composting.